Mary Church Terrell (1863-1954): A Black Woman Pioneer Historian: From the Margin to the Center Stage - Fatma Ramdani (IdeAs)
This article seeks to render to Mary Church Terrell, one of the best educated black women leaders of her day, her long overdue recognition as a historian. It will demonstrate that Mary Church Terrell was a groundbreaking historian by bringing to light the stories and experiences of her marginalized community and in particular of black women’s dual exclusion from American society. The first part of this article, an analysis of her life trajectory, will shed light on her understanding of the significance of making African American women’s contributions more visible and part of both African American and women history. An overview at her career as a journalist, as both witness and actor, intellectual and social activist will then be carried out. For the purpose of this article, I will focus on four articles written by Mary Church Terrell which showcase her pragmatic approach to history. She aimed at presenting a new interpretation of salient issues of her time, such as lynching, from the perspective of a black woman. Finally, a special focus on her self-published autobiography, A Black Woman Living in a White World (1940), a detailed and compelling testimony of a black woman living in segregated America, will show that her pioneering and audacious endeavor was a successful attempt at moving black women to a central position in American historiography.